The Effects of Transcranial Direct Current Stimulation on Balance and Gait in Stroke Patients: A Systematic Review and Meta-Analysis - Dong, Ke; Meng, Shifeng; Guo, Ziqi; Zhang, Rufang; Xu, Panpan; Yuan, Erfen; Lian, Tao (Frontiers in Neurology, 2021)
Objective: Balance dysfunction after stroke often results in individuals unable to maintain normal posture, limits the recovery of gait and functional independence. We explore the short-term effects of transcranial direct current stimulation (tDCS) on improving balance function and gait in stroke patients. Methods: We systematically searched on PubMed, Web of Science, EMBASE, Cochrane Central Register of Controlled Trials, and Google Scholar for studies that explored the effects of tDCS on balance after stroke until August 2020. All involved studies used at least one measurement of balance, gait, or postural control as the outcome. Results: A total of 145 studies were found, of which 10 (n = 246) met the inclusion criteria and included in our studies. The present meta-analysis showed that active tDCS have beneficial effects on timed up and go test (TUGT) [mean difference (MD): 0.35; 95% confidence interval (CI): 0.11 to 0.58] and Functional Ambulation Category (FAC) (MD: −2.54; 95% CI: −3.93 to −1.15) in stroke patients. However, the results were not significant on the berg balance scale (BBS) (MD: −0.20; 95% CI: −1.44 to 1.04), lower extremity subscale of Fugl-Meyer Assessment (FMA-LE) (MD: −0.43; 95% CI: −1.70 to 0.84), 10-m walk test (10 MWT) (MD: −0.93; 95% CI: −2.68 to 0.82) and 6-min walking test (6 MWT) (MD: −2.55; 95% CI: −18.34 to 13.23). Conclusions: In conclusion, we revealed that tDCS might be an effective option for restoring walking independence and functional ambulation for stroke patients in our systematic review and meta-analysis. Systematic Review Registration: CRD42020207565.